ANALISIS TEORI AROUSAL DAN PERTIMBANGAN SOSIAL (SOCIAL JUDGEMENT) TERHADAP MANTAN ANGGOTA GAFATAR DI KABUPATEN LEBAK PROVINSI BANTEN (Penamas, 2018)
This research was conducted on former Gafatar member in Lebak regency, Banten province, in 2016. The study was conducted using a qualitative approach and took the research subject as a case studied from a family that attracted enough public attention in the district. The results showed that the joining of the research subject with Gafatar was based on a desire (vision) to change lives (it moved; arousal dopamine neurotransmitters in the limbic system of the brain). This is the basis of the frame of cognition of research subjects in achieving ideal balance. The decision to prove the truth by supporting the program promoted by Gafatar. And increasingly strengthened as a result of the intensity of communication that was built by the Gafatar management of research subjects. Researchers suggest that those who care, especially the government, to realize a real social work as a good pilot for the community. And local governments (such as RTs and RWs) always carry out dialogues with their citizens in each region as a place to gather information from a number of issues that are being felt by the community. Keywords: Gafatar, Lebak-Banten Regency, Arousal Theory and Social Judgment Theory.